Czasownik mentalny (nie) rozumiem w audycji radiowej Dzieci wiedzą lepiej - Ożdżyński, Grzegorz (ANNALES UNIVERSITATIS PAEDAGOGICAE CRACOVIENSIS. STUDIA LINGUISTICA, 2013)
The author analyses utterances of pre-school children focusing on metalinguistic sentences, i.e. sentences that contain the negative predicate to not understand. His observations confirm the thesis put forward by other scholars that children at this level of development can understand and produce acceptable utterances, i.e. utterances that fit the context. In other words, the ability of pre-school children to understand is better developed that their ability to express themselves.